ANALISIS PENGARUH KREDIBILITAS KEBIJAKAN MONETER TERHADAP VOLATILITAS BI RATE DAN PERSISTENSI INFLASI (STUDI KASUS PADA REZIM INFLATION TARGETING DI INDONESIA) - Pradhani, Tri Buana Wira (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The credibility of monetary policy is crucial for the successful implementation of monetary policy to control low and stable inflation. The purpose of this research is to determine the impact of the credibility of monetary policy on the volatility of the BI rate and persistence of inflation. The results show that during the implementation of Full-Fledged Inflation Targeting (2005:7 - 2015:12), the credibility of monetary policy has a significant effect on the volatility of the BI rate and inflation persistence. The results also show that the level of credibility of monetary policy in Indonesia is high, that is 80% and inflation persistence level is very low, that is 5.5%. This is because economic actors in Indonesia begin to behave forward looking, so expectations of inflation will refer to the inflation target that has been established.Keywords: Inflation Targeting, credibility of monetary policy, volatility of the BI rate, persistence of inflation